Public Sector Organisations as Corporate Citizens - Norris, Christopher Michael (2006)
In light of the launch by the Department of Health and the Sustainable Development Commission of the NHS Good Corporate Citizenship Assessment Model, this research explores the application of Corporate Citizenship to public sector organisations. The paper begins with a review of literature on the conceptualisation of Corporate Citizenship and Sustainable Development, including the interplay with the set of ideas labelled New Governance. It also considers previous research into the economic case for the use of public funds to further sustainable development in the light of the UK Government's Sustainable Development Strategy, alongside research into the challenge of managing for public health in the NHS.